Analysis of the Impact of Welding on Air Quality and Public Health in Indonesia - Sabaruddin Rahman (Collaborate Engineering Daily Book Series, 2023)
Welding is a process that produces gas and particulate emissions that can affect air quality and public health. This study aimed to analyze the impact of welding on air quality and public health in Indonesia, using data from various sources and statistical methods. The results showed that welding increased the concentration of air pollutants such as PM2.5, PM10, NO2, SO2, O3, and CO in several big cities in Indonesia, especially Jakarta, Surabaya, Bandung and Medan. Welding also harms public health by increasing the risk of respiratory, cardiovascular disease, lung cancer and neurological disorders. This study recommends several steps to reduce the impact of welding on air quality and public health in Indonesia, such as using welding technology that is more environmentally friendly, implementing strict emission standards, monitoring and controlling air quality, and increasing public awareness and education about the dangers of welding.